Sonoelastography Usage Among German DEGUM-Certified Breast Ultrasound Specialists - Wojcinski, S.; Degenhardt, F.; Peisker, U.; Beussel, S.; Hahn, M. (Ultraschall in der Medizin - European Journal of Ultrasound, 2014)
Purpose: Sonoelastography of the breast is an emerging technology with evident data in the literature suggesting diagnostic advantages. Our study investigates the current usage of sonoelastography among German DEGUM-certified breast ultrasound specialists.Materials and Methods: We used a standardized questionnaire with 18 items. In 2012, the survey was sent to all members of the breast ultrasound section of the DEGUM (n = 654).Results: The group of survey participants (n = 208) performs 193 025 breast ultrasound examinations and examines 20 110 breast cancers per year. 21.2 % of the participants in the survey use sonoelastography, mainly for diagnostic purposes in BI-RADS®-US 3 and 4 lesions, less often for other categories or under study conditions. The most commonly applied criteria for the evaluation of the elastogram are the Tsukuba Elasticity Score (43.2 %), the fat-lesion ratio (29.5 %) and the determination of tissue stiffness with shear wave elastography expressed in kilopascal (25.0 %). The majority of non-users of elastography (58.6 %) would like to have the option of using sonoelastography in the future.Conclusion: Sonoelastography is a feasible and helpful method in the evaluation of breast lesions. A significant number of German ultrasound specialists already apply this technology today. We expect a growing number of sonographers to perform sonoelastography in the near future, provided that they have the necessary ultrasound system and that they are trained in the method. Evidence from the literature and the recommendations of the medical societies support this development.
Keywords: breast; ultrasound; technical aspects